The Role of Fan Speed and Misting for Computational Fluid Dynamics (CFD) Analysis of Temperature and Humidity Regulation in Greenhouses - Renny Eka Putri; Mutiara Salwa; Ashadi Hasan; Irriwad Putri (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Maintaining an optimal climate is essential for plant growth, and greenhouses though controlled often face challenges such as excessive heat. To address this, fan and misting systems are commonly used. This study investigates the role of fan speed and misting in regulating temperature and relative humidity (RH) in a smart greenhouse using Computational Fluid Dynamics (CFD) simulations. In this research, CFD simulations were performed using actual temperature and RH measurements as input data. The scenarios included varying fan speeds (3.4 m/s, 4.5 m/s) and a control condition without a fan, combined with 15-minute misting sessions. The results show that a fan speed of 4.5 m/s with misting is more effective at lowering temperature compared to 3.4 m/s under the same misting conditions. The simulation errors were below 10% across all treatments, indicating the model’s reliability. These findings offer valuable insights for optimizing climate control in greenhouses, supporting more efficient and sustainable crop production.